DINAMIKA PENGARUH MEDIA SOSIAL TERHADAP KEHARMONISAN RUMAH TANGGA DALAM PERSPEKTIF HUKUM KELUARGA - Maulina, Nia; Hidayat, Rahmat; Irwansyah, Wawan; Wiranti, Wiranti; Fatihatu Salamah, Nur (Penerbit Lafadz Jaya, 2025)
Social media has become an integral aspect of modern household life, offering both opportunities and challenges to family harmony. While platforms enable smoother communication between spouses, they also introduce risks such as jealousy, suspicion, and conflict due to interactions with individuals outside the marital relationship. This study analyzes the influence of social media on household harmony from the perspective of Islamic family law and explores how Muslim families resolve related conflicts. Using a qualitative method, the research involves in-depth interviews with Muslim couples, religious leaders, and family mediators in urban and semi-urban areas of West Kalimantan. The data were processed through stages of reduction, presentation, and verification, and interpreted in light of Islamic family law principles. The findings show that social media has a dual role in household dynamics. While some couples benefit from enhanced communication and emotional closeness, others experience discord triggered by breaches of privacy or inappropriate interactions. Most conflict resolution is conducted internally through mutual dialogue or with the involvement of religious figures. The principles of reconciliation and adherence to Islamic values are central to resolving disputes. The study highlights the need for integrating digital literacy grounded in Islamic teachings into premarital counseling and family guidance. It provides insights for religious counselors, mediators, and policymakers seeking to strengthen family resilience in the digital era. This research offers a distinctive contribution by focusing on the intersection of social media use and Islamic family law in the local context of West Kalimantan, an area that remains underexplored in previous studies.